Universal implantation of temporary epicardial pacing wires after surgery for congenital heart disease: necessity or luxury?. (24th October 2019) - Perumal, Gopinath; Marathe, Supreet Prakash; Betts, Kim S; Suna, Jessica; Morwood, Jim; Wildschut, Jason; Mattke, Adrian C; Alphonso, Nelson; Venugopal, Prem
Abstract: : OBJECTIVES: Routine implantation of temporary epicardial pacing wires after surgery for congenital heart disease (CHD) has recently been questioned. We evaluated the incidence of arrhythmias, arrhythmias causing haemodynamic compromise and the safety of a strategy of selective implantation of pacing wires in our unit. METHODS: All patients who underwent surgery for CHD using cardiopulmonary bypass between September 2015 and December 2016 were retrospectively enrolled in the study ( n = 313). Patients were stratified into group A (universal implantation) and group B (selective implantation). Group B received pacing wires only when postoperative rhythm disturbances were anticipated based on the operating surgeon's judgement. The primary outcome was arrhythmia causing haemodynamic compromise. Outcomes were compared between unmatched and propensity matched groups. RESULTS: Forty-eight patients experienced an arrhythmia causing haemodynamic compromise (15.3%). Twenty-three patients (7.3%) experienced an arrhythmia causing haemodynamic compromise that required the use of pacing wires for therapeutic purposes (group A n = 13, group B n = 10, P = 0.34). There were no pacing wire related complications in either group. All patients in group A and 90% in group B had pacing wires when needed ( P = 0.435). In group A, 89% of patients had pacing wires which were not used compared with 13% in group B ( P < 0.001). Results were unchanged when repeated using propensity matching (81 pairs). CONCLUSIONS: The probability of developing a postoperative arrhythmia requiring therapeutic pacing can be predicted using the risk factors identified in our study. The routine implantation of pacing wires after surgery for CHD is not necessary. A measured reduction from universal implantation is safe.